O coensino para a inclusão de estudantes com transtorno do desenvolvimento intelectual: intervenções colaborativas para a formação de professores no Centro de Ensino “Professor José do Nascimento Morais” - RIBEIRO, Arleia Gomes de Sousa (2024)
This research aimed to investigate the actions related to co-education, in order to propose educational interventions with teachers in support of the Inclusive Education of students with Intellectual Development Disorder (TDI), with a view to the construction of an E-book that can help the teachers of the regular education of a high school of the state network in São Luís – MA. As for the methodological aspects, they are classified as of an applied nature, according to the approach to the problem, and characterized as qualitative of the intervention type. The field of investigation was the Teaching Center "Professor José do Nascimento Morais", a state school in the Vinhais neighborhood, in São Luís – MA, and had as participants the teachers of regular education, the teacher of the appeal room and the pedagogical coordination. The instruments for data collection were questionnaires and semi-structured interviews. The collected data were analyzed according to the content analysis technique. The results obtained showed that 83% of the sample investigated had little experience in Inclusive Education for students with disabilities, although 77.7% of them had extensive experience in the classroom, but that they did not develop in their practices actions that meet the student with TDI, and in addition, 40% of the sample studied had carried out continuing education in inclusive education or flexibilization activities with students with TDI. From the main findings of the research and the results, it was evident the need for continuing education for teachers and pedagogical coordination of that school, which results in collaborative and inclusive pedagogical practices, in order to ensure new learning possibilities for students with TDI, as well as to provide, to participating educators, new educational strategies through the product of this research: Pedagogical Guidelines on Co-education and Curricular Flexibilizations in Support of the Inclusion of Students with Intellectual Development Disorder.